Kajian Deskriptif Bentuk dan Makna Reduplikasi dalam Bahasa Sasak Dialek Ngeto-Ngete - Roziana, Yulita; Baiq Gina Haqiqah; Lia Kamelia; Desta Ariska; Dea Septia Aulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms and meanings of reduplication in the Sasak language, specifically the ngeto-ngete dialect spoken by its native community in West Nusa Tenggara. The research employs a descriptive qualitative approach, with data obtained from the spoken utterances of native speakers of the ngeto-ngete dialect.data were analyzed through several stages, including the identification of reduplication forms, classification of reduplication types, analiysis of grammatical meanings, and drawing conclusions based on relevant morphological theories. The findings reveal that reduplication in the Sasak ngeto-ngete dialect consists of four forms: full reduplication, partial reduplication, phoneme-changing reduplication, and affixed reduplication. Furthermore, these reduplication forms convey several grammatical meanings, such as plural meaning, partial or intensity meaning, and unconditional meaning. These findings indicate that reduplication functions not only as a word-formation process but also plays an important role in enriching grammatical meaning and linguistic expression in the Sasak ngeto-ngete dialect. This study is expected to contribute to linguistic studies, particularly in the field of regional language morphology, and to serve as a reference for further research.